Eksplorasi Eksistensi Tradisi Ngidang-Ngobeng dalam Perspektif Civic Culture Generasi Muda Palembang - Mariyani Mariyani; Rahmat Rahmat; Husnul Fatiha (Jurnal Humanitas: Katalisator Perubahan dan Inovator Pendidikan, 2025)
The ngidang-ngobeng tradition is an intangible cultural heritage of the people of Palembang that reflects the values of mutual cooperation, social equality, and community solidarity through the practice of serving food and eating processions together. This tradition functions as a social space that strengthens relationships between citizens, forms a collective identity, and fosters a sense of togetherness across generations. However, in the midst of modernization and globalization, the participation of the younger generation in this tradition has decreased significantly. This study uses a phenomenological approach to explore the lived experience of the  younger generation towards ngidang-ngobeng , as well as identify factors that support or hinder its preservation. Data were obtained through in-depth interviews, participatory observations, and documentation of three indigenous youth informants from Palembang using purposive sampling techniques. The results show that although symbolic understanding of tradition is still strong as a symbol of respect, togetherness, and family values, changes in lifestyle, perception, efficiency, and the influence of digital technology cause the involvement of the younger generation to tend to decrease. This tradition is considered impractical and irrelevant to the rhythm of modern life. Nevertheless, ngidang-ngobeng still has great potential as a medium of citizenship education based on local culture, which instills values such as participation, solidarity, tolerance, and social responsibility. This study confirms the importance of adaptive, participatory, and contextual conservation strategies, involving young people as key actors. With a creative and value-based approach, these traditions can continue to live on as dynamic, relevant, and meaningful cultural practices in the lives of contemporary societies.